2020
DOI: 10.1186/s12904-020-00583-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding family caregivers’ needs to support relatives with advanced progressive disease at home: an ethnographic study in rural Portugal

Abstract: Background: Family caregivers play an important role supporting their relatives with advanced progressive disease to live at home. There is limited research to understand family caregiver needs over time, particularly outside of high-income settings. The aim of this study was to explore family caregivers' experiences of caring for a relative living with advanced progressive disease at home, and their perceptions of met and unmet care needs over time. Methods: An ethnographic study comprising observations and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Moreover, previous research states that family caregivers are reluctant to seek external support because they do not want to disclose family-related problems due to a sense of pride, 47 , 48 but are also reluctant to accept help from other family members. 49 Additionally, Willemse et al 46 found that information on the possibilities was often lacking, and they stressed the necessity of proactively informing caregivers. 46 Over the past years, multiple interventions have been described to support family caregivers in their role as a caregiver and to eventually reduce their perceived burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, previous research states that family caregivers are reluctant to seek external support because they do not want to disclose family-related problems due to a sense of pride, 47 , 48 but are also reluctant to accept help from other family members. 49 Additionally, Willemse et al 46 found that information on the possibilities was often lacking, and they stressed the necessity of proactively informing caregivers. 46 Over the past years, multiple interventions have been described to support family caregivers in their role as a caregiver and to eventually reduce their perceived burden.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to, as a care professional, proactively inform the informal caregiver about their options for support and offer a tailor-made, personal approach with enough room to participate in the care process when this is preferred by the informal caregiver. 49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The older person’s relatives contribute significantly to the quality of home-based palliative care [ 14 ]. However, they reportedly often feel unprepared to perform caregiving tasks, experiencing a heavy burden that impacts both their emotional and physical health [ 15 17 ]. Including relatives when developing and revising care plans might therefore increase their satisfaction with the care delivered to patients and better prepare them for the terminal phase [ 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, introducing a standardized, self-reported caregiver supplement to the current interRAI suite would help understand their source of distress, needs and challenges, and navigate support services [ 26 ]. Routine screening and assessment of psychological and physical health needs, as well as preventive measures oriented towards informal caregivers across their caregiving journey, should be core elements of optimal family-centered and community-based care [ 2 , 3 , 6 , 10 , 17 , 27 29 ].…”
mentioning
confidence: 99%